Role Conflict Memoderasi Locus Of Control dan Kompleksitas Tugas terhadap Perilaku Penyimpangan Auditor Akuntan Publik - Ardini, Ririn; Nofryanti, Nofryanti; Rosini, Iin (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study was to test and analyze whether locus of control role conflict and task complexity affect audit deviation behavior. This study uses a quantitative approach with a questionnaire survey model given to junior auditors, senior auditors, supervisors, managers, partners at the Public Accounting Firm in West Jakarta. The questionnaire that was processed was 128 respondents. Analysis using structural equation modeling (SEM) PLS Version.3.This study shows that locus of control has a positive effect on audit deviation behavior. Task complexity has a positive effect on audit deviation behavior. Moderating locus of control role conflict on audit deviation behavior and moderating task complexity role conflict on deviation behavior.